A NOVEL METHOD TO ESTIMATE LYMPHOCYTE DOSE AND APPLICATION TO PEDIATRIC AND YOUNG ADULT CT PATIENTS IN THE UNITED KINGDOM. Issue 1 (28th July 2017) - Lee, Choonsik; Morton, Lindsay M; de Gonzalez, Amy Berrington
Abstract: Despite decades of epidemiological research, it remains uncertain whether ionizing radiation can cause lymphomas. Most epidemiological studies of lymphoma risk following non-uniform exposure used dose to red bone marrow (RBM), constituting a small fraction of the lymphocytes, as a surrogate of dose to the lymphocytes. We developed a method to estimate dose to the lymphocytes using the reference distribution of lymphocytes throughout the body and Monte Carlo simulations of computational human phantoms. We applied our method to estimating lymphocyte doses for a pediatric CT patient cohort in the United Kingdom. Estimated dose to the RBM was greater than lymphocyte dose for most scan types (up to 2.6-fold higher, a 5-year-old brain scan) except abdomen scan (RBM dose was about half the lymphocyte dose, a 5-year-old abdomen scan). The lymphocyte dose in the UK cohort showed that T-spine and whole body scans delivered the highest lymphocyte doses (up to 22.4 mGy).